Improving electricity supply in Nigeria-potential for renewable energy from biomass - Saifuddin N.; Bello S.; Fatihah S.; Vigna K.R. (Research India Publications, 2023)
Achieving sustainable energy development requires rational use of energy resources and technologies, and the development of appropriate policies. There is a huge deficit in supply of energy and this has become a major limitation to growth and quality of life. The developing nations of Africa are popular locations for the application of renewable energy technology. Nonetheless, largely remain untapped as a consequent of unconductive business environment; Nigeria faces a number of challenges across its energy triangle. It needs to address an acute energy deficit. At present, power generation is<5000MW and apparently the country is not maximizing its human and natural resource potentials. The application of renewable energy technology has the potential to alleviate many of the problems that face Africans every day, especially if done so in a sustainable manner. The oil palm in general is the most productive crop in terms of oil yield. It also generates more than 200 tons of waste biomass (solid and liquid). Oil palm has great potential for application in the biofuel industry for Nigeria. Solving the electricity crisis must remain at the very top of the Policy-makers agenda and thus, the need for a study such as this. The review paper sought to examine the challenges preventing the progress of accessible electricity in Nigeria. The paper also looks at the potential of palm oil industry as being a major contributor to the renewable energy mix for Nigeria using Malaysia as the role model. Research India Publications.